Record of SwainsonÂ´s warbler (Limnothlypis swainsonii) in northern South America - Casler, Clark; Esté, Elsie (Boletín del Centro de Investigaciones Biológicas)
A sighting of Swainson’s Warbler (Limnothlypis swainsonii) in mangrove forest, east of Maracaibo, western Venezuela, on 02 February 1994, represents a new record for Venezuela and South America. This migratory warbler was not known to occur south of Honduras.